Depth Gradient and Radon Activity Concentration in Soil Gas in the Zone of a Potentially Active Fault - Timofey Leshukov; Konstantin Legoshchin; Kirill Avdeev; Elizaveta Baranova; Aleksey Larionov (Earth)
The study specifies the changes in radon activity concentration (RAC) in soil gas with depth and emphasizes the significance of the meteorological factor for deeper boreholes. Radon activity concentration was measured in 0.6 m, 1 m and 1.5 m boreholes, and the depth gradient was also calculated. Spatial patterns were estimated using an autocorrelation index. RAC ranged from 9454 ± 439 Bq/m3 for 0.6 m, 16,031 ± 602 Bq/m3 for 1 m and 22,049 ± 937 Bq/m3 for 1.5 m. RAC increased with depth at most of the study sites and behaved quite uniformly in spatial terms. At the same time, no significant differences in the activity of uranium (238U) series isotopes at different soil depths were detected. Significant spatial variability in radioactivity and the physical properties of soils is noted. The highest gradient was between 0.6 and 1 m. It was found that with increasing depth the connection between the RAC and the meteorological conditions (temperature and humidity) of the surface layer of the atmosphere is lost. It follows that for shallow boreholes it is necessary to consider the influence of meteorological conditions. RAC in 1 m boreholes correlates with 1.5 m and 0.6 m boreholes, but no correlation was found for the 1.5 m and 0.6 m boreholes themselves. Thus, 1 m boreholes are optimal for radon monitoring. A high level of RAC indicates a high potential for indoor radon exposure in this territory, with corresponding epidemiological consequences in the long term.